The economic costs of climate change: A multi-sector impact assessment for Vietnam - Arndt, Channing; Tarp, Finn; Thurlow, James (MDPI, 2015)
We adopt a multi-sectoral approach and consider the full range of climate projections. Biophysical damages are translated into economic costs using a dynamic economy-wide model. Our results indicate that the negative impacts on agriculture and roads are modest to 2050. Larger costs are caused by rising sea levels and cyclone strikes. Overall, climate change is likely to reduce national income by between one and two percent by 2050 (relative to a historical baseline). Damages double under more extreme projections. Our findings suggest that there are net benefits from selected pre-emptive actions though careful consideration of opportunity costs is required.